The Lisbon Treaty and the British Press: A Corpus-based Contrastive Analysis of Evaluation Resources - Nasti, Chiara; Venuti, Marco (Research in Language, 2014)
This paper is based on the results of an earlier research which has proved that metaphors can be employed by the British press to construe the event of the Lisbon treaty ratification and might be a useful linguistic tool to explore different attitudes towards that event (Nasti 2010). On the premises that metaphors are connected to evaluation as they are manifestations of the writer’s or speaker’s intentions, the present paper will investigate those evaluative resources that have been found to co-occur with the metaphors previously analyzed in order to explore how the British press uses these resources to construe the event of ratification and to what extent it presents a similar description or attributes similar roles to the European leaders. This paper is divided into six sections. The first section provides a general overview of the main stages towards the ratification of the Lisbon Treaty. The second, after giving a definition of evaluation, briefly describes the results of the previous research. The third part provides information on data collection and the theoretical background. The fourth and the fifth sections deal with the analysis of the evaluative lexis. The conclusions indicate that metaphors and evaluation are both used to create a coherent text and image of the ratification issue.